Some amendments to three votive altars from the conventus Bracaraugustanus (Hispania Citerior): a new attestation of the goddess Nabia, the castellum Durba and the Dacori, an unknown civitas (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2022)
This paper analyzes three votive inscriptions preserved in the Pio XII Museum, from Braga, and the Martins Sarmento Museum, from Guimarães. The study of these three monuments starts from an autopsy on the ground, from which it has been concluded that the readings offered so far are not correct. The first votive altar was considered by the preceding editors as an offering to an unknown deity which has an epithet also unpublished. Our study establishes that it is a dedication to the well-known Lusitano-Galician goddess Nabia, which reinforces the solidity of the goddess cult in Bracara Augusta, as noted in the well-known sanctuary of the “Fonte do Idolo”. The second piece, although it allows us to make changes in the name of the deity, is of great importance because the reference to an unknown civitas appears: the civitas Dacorum. In addition, the name of a castellum that belonged to this civitas is established, the Durba castellum, already cited in another inscription and also as an appellation of a deity from the conventus Bracaraugustanus: Durbedicus. The proposed changes for the third monument are less relevant, since only the name of the venerated deity is modified.